THE EFFECT OF USING THE POWER OF TWO MODEL TOWARD STUDENT’S WRITING ABILITY AT VIII GRADE IN SMPN 1 BANGKO AKADEMIC YEAR 2018/2019 - Eki Kurniawan (Universitas Jambi, 2018)
This study aim to identify and describe the effect of the Power of Two model towards students’ writing ability at VIII grade SMPN 1 MERANGIN academic year 2018/2019. This research was quasi-experimental design with the posttest-only design. The design that was consisted of some groups, the first group was given the treatment (X) and the other group did not. The Power of Two model as the independent variable and the writing ability as a dependent variable. Population was all the VIII grade students of SMPN 1 Bangko as much as 3 classes that consisted of 80 students. The sampling technique used Cluster Sampling. The selected sample is VIII A class as the experimental class and the control class VIII B. The data was collected by using test on the material to write a narrative text. The results of the analysis of the test data obtained by the average of the experimental class 60,75, variant 209,04 and standard deviation 14,80, data obtained while the control class 59,33, variant 179,02, and standard deviation 13,38. Hypothesis test results obtained, ≥ 1, 99 this research is a significant difference between the Power of Two model towards students’ writing ability at VIII grade in SMPN 1 Bangko academic year 2018/2019. Therefore, it is expected that administer special educators teaching English to be able to use the Power of Two models for writing narrative text. Key words: Writing Ability and the Power of Two Model